Draft genome of six Cuban Anolis lizards and insights into genetic changes during their diversification - Shunsuke Kanamori; Luis M. Díaz; Antonio Cádiz; Katsushi Yamaguchi; Shuji Shigenobu; Masakado Kawata (BMC Ecology and Evolution, 2022)
Abstract Background Detecting genomic variants and their accumulation processes during species diversification and adaptive radiation is important for understanding the molecular and genetic basis of evolution. Anolis lizards in the West Indies are good models for studying evolutionary mechanisms because of the repeated evolution of their morphology and the ecology. We performed de novo genome assembly of six Cuban Anolis lizards with different ecomorphs and thermal habitats (Anolis isolepis, Anolis allisoni, Anolis porcatus, Anolis allogus, Anolis homolechis, and Anolis sagrei). We carried out a comparative analysis of these genome assemblies to investigate the genetic changes that occurred during their diversification. Results We reconstructed novel draft genomes with relatively long scaffolds and high gene completeness, with the scaffold N50 ranging from 5.56 to 39.79 Mb and vertebrate Benchmarking Universal Single-Copy Orthologs completeness ranging from 77.5% to 86.9%. Comparing the repeat element compositions and landscapes revealed differences in the accumulation process between Cuban trunk-crown and trunk-ground species and separate expansions of several families of LINE in each Cuban trunk-ground species. Duplicated gene analysis suggested that the proportional differences in duplicated gene numbers among Cuban Anolis lizards may be associated with differences in their habitat ranges. Additionally, Pairwise Sequentially Markovian Coalescent analysis suggested that the effective population sizes of each species may have been affected by Cuba’s geohistory. Conclusions We provide draft genomes of six Cuban Anolis lizards and detected species and lineage-specific transposon accumulation and gene copy number changes that may be involved in adaptive evolution. The change processes in the past effective population size was also estimated, and the factors involved were inferred. These results provide new insights into the genetic basis of Anolis lizard diversification and are expected to serve as a stepping stone for the further elucidation of their diversification mechanisms.